Macrophages in chronic infections: regulation and remodeling - Cui, Hongle; Wang, Min; Jiao, Sitan; Tian, Sirui; Liu, Hui; Luo, Bo (Frontiers in Immunology, 2025)
Macrophages, as a critical component of innate immune cells, exhibit significant plasticity. When confronted with danger signals such as pathogens or microenvironmental alterations, macrophages can differentiate into various phenotypes and functions to safeguard the host. However, numerous pathogens manipulate macrophage metabolic pathways to modify their functional expression, facilitating immune evasion and ensuring long-term survival during chronic infections. Therefore, the role of macrophage metabolic reprogramming in chronic infections has received growing attention. This review elucidates the primary metabolic pathways of macrophages and their association with polarization. It examines how pathogens modulate macrophage functional expression through metabolic reprogramming to sustain chronic infection. Additionally, it delineates how macrophage metabolic reprogramming in chronic infections reconfigures the microenvironment through interaction with other immune cells and its contribution to trained immunity.